High-temperature-resistant and impact-resistant silicon foam material as well as preparation method and application thereof

By using ceramic composite fillers with multi-grade particle size structures and low-temperature domain flux in silicon foam materials, the problems of impact resistance and heat insulation effects of materials at high temperatures and combustion are solved, and efficient ceramic and cell structure optimization is achieved.

CN119592081APending Publication Date: 2025-03-11SHANGHAI KETER POLYMER MATERIAL +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411952096.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing silicon foam materials cannot effectively maintain impact resistance and heat insulation during high temperatures and combustion, and high added amounts of porcelain fillers affect the foaming conditions and flame retardant properties.

Method used

By combining ceramic composite fillers with multi-stage particle size structure and low-temperature domain fluxes with different melting temperatures, the ceramic formation effect and cell structure of silicon foam materials are optimized to ensure that the material maintains impact resistance and heat insulation at high temperatures.

Benefits of technology

The silicon foam material is achieved after firing at 800°C for 10 minutes, forming a complete ceramic body, with a smooth surface, maintaining a good cell structure and impact resistance, and having good thermal insulation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215099520000121
    Figure BDA0005215099520000121
  • Figure BDA0005215099520000131
    Figure BDA0005215099520000131
  • Figure BDA0005215099520000141
    Figure BDA0005215099520000141
Patent Text Reader

Abstract

The invention relates to the technical field of silicon rubber, in particular to a high-temperature-resistant and impact-resistant silicon foam material as well as a preparation method and application thereof. Comprising the following raw materials in parts by weight: 20-30 parts of vinyl silicone oil, 5-10 parts of hydrogen-containing silicone oil, 40-50 parts of a foaming agent, 5-10 parts of a reinforcing filler, 10-12 parts of a flame-retardant filler, 15-20 parts of a ceramic composite filler, 0.05-0.2 part of an inhibitor and 0.5-2 parts of a catalyst, wherein the ceramic composite filler is selected from a combination of modified glass powder, other ceramic forming fillers and zinc borate; the modified glass powder is low-temperature domain glass powder; and the other ceramic forming fillers are in multi-stage particle size grading. By matching the ceramic forming filler with a multistage particle size structure, plane accumulation with maximum ceramic forming points is formed on a silicon foam organic layer, and low-temperature domain fluxing agents with different melting point temperatures are selected to participate in generation of a continuous phase, so that the phenomenon of cracks caused by loss of skeleton particles due to massive decomposition of the organic phase is reduced, and the silicon foam material subjected to high-temperature calcination is complete in foam structure and high in strength. High-temperature resistance, heat insulation and impact resistance are high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicone rubber, and in particular to a high-temperature resistant and impact-resistant silicone foam material and a preparation method and application thereof. Background Art

[0002] The key factors that restrict the development of new energy vehicles are the endurance and safety performance of power batteries, among which the safety performance of batteries is of utmost importance, which is related to the life safety of drivers and passengers. Power batteries face complex use environments during use. Mechanical impact, high temperature, water immersion, battery short circuit and other situations will cause power batteries to be damaged and unable to work normally. In severe cases, thermal runaway, spontaneous combustion and even explosion will occur, threatening people's life safety. Therefore, the protective materials of power battery packs must have good buffering, shock absorption, flame retardant and heat insulation properties.

[0003] Silicone foam is a foam material formed by chemical foaming to produce hydrogen. Due to the main chain -Si-O-Si-structure, silicone foam has good elasticity, low stress, compression permanent deformation resistance and weather resistance. It is widely used as a buffer sealing material in new energy power batteries, but it is a bit difficult to use it as a flame retardant and heat-insulating material. The key reason is that during the combustion process of the foam, after the organic material and inorganic flame retardant powder are burned, only a nearly powdered and poorly-strength silicon dioxide layer will remain, which cannot really achieve the effect of heat insulation. In order to expand the application of silicone foam in heat insulation, it is necessary to introduce a ceramic reaction into the silicone foam, so that the silicone foam can quickly undergo a ceramic reaction at a certain temperature during the combustion process to form an impact-resistant material with a supporting structure. At a high temperature of more than 1000°C, it can still maintain a hard impact-resistant shell with no cracks on the surface. At the same time, the foam pore structure is strengthened, and a low thermal conductivity is maintained to block heat transfer, giving the silicone foam material good thermal insulation properties.

[0004] At present, in order to ensure that silicone foam has good ceramic properties, a high addition of ceramic fillers is selected. However, the high addition will affect the foaming of the silicone foam, resulting in difficulty in foaming the system or uneven pores, low foaming ratio, increased foam density, and high addition of ceramic fillers will inevitably affect the addition ratio of flame retardant powder, resulting in poor flame retardant properties of the foam, which violates the design concept of safety and lightweight power batteries for new energy vehicles and limits the industry application of silicone foam materials in the fields of automobiles, aviation, rail transit, etc. Summary of the invention

[0005] In view of the shortcomings of the prior art mentioned above, the purpose of the present invention is to provide a high temperature resistant and impact resistant silicone foam material and a preparation method and application thereof. By matching a ceramic composite filler with a multi-level particle size structure and further preferably using a low temperature domain flux with different melting temperatures, while ensuring the addition of a small amount of ceramic filler, the material is given good impact resistance, and the silicone foam still has good flame retardant properties. During the entire foaming process, the pores are closed, the pores are evenly distributed, and the pore size is consistent.

[0006] To achieve the purpose of the invention, the following technical solutions can be used:

[0007] The present invention provides a high temperature resistant and impact resistant silicone foam material, which comprises the following raw materials in parts by weight: 20-30 parts of vinyl silicone oil, 5-10 parts of hydrogenated silicone oil, 40-50 parts of foaming agent, 5-10 parts of reinforcing filler, 10-12 parts of flame retardant filler, 15-20 parts of ceramic composite filler, 0.05-0.2 parts of inhibitor, and 0.5-2 parts of catalyst. The ceramic composite filler is selected from a combination of modified glass powder, other ceramic fillers, and zinc borate; the modified glass powder is low temperature domain glass powder; and the other ceramic fillers are multi-grade particle size grading.

[0008] The present invention also provides a preparation method of the high temperature resistant and impact resistant silicone foam material as described above in the present invention, the preparation method comprising: stirring and mixing vinyl silicone oil, hydrogen silicone oil, foaming agent, reinforcing filler, flame retardant powder, and ceramic composite filler for the first time, then adding an inhibitor for the second stirring and mixing, and then adding a catalyst, stirring and mixing for the third time to obtain a uniformly dispersed rubber material; the uniformly dispersed rubber material is calendered by a coating tool, and is cured by sulfur and reinforced by secondary vulcanization to obtain a high temperature resistant and impact resistant silicone foam material.

[0009] The present invention also provides the use of the high temperature resistant and impact resistant silicone foam material as described above in the present invention and / or the high temperature resistant and impact resistant silicone foam material prepared by the preparation method as described above in the field of protective materials for power battery packs of new energy vehicles.

[0010] By adopting the above technical solution, the beneficial effects of the present invention are:

[0011] (1) The present invention is based on the principle of multi-level particle size grading. By selecting a plurality of (for example, three) ceramic particles of different particle sizes, the ceramic powder particles with smaller particle sizes will be accumulated in the gaps between the ceramic powder particles with larger particle sizes under the strong shear force of the planetary agitator, thereby ensuring that the ceramic powder can form the largest plane accumulation during the combustion process of the organic layer of the silicon foam, forming a sufficient number of ceramic points and a complete ceramic layer, thereby ensuring that the silicon foam material has a sufficiently strong porcelain body strength. Figure 1It is an ideal atomic stacking model. It can be seen from the figure that there are gaps in the center and the center of the side of the model. In these gaps, porcelain-forming points are missing. These gaps can be filled with porcelain-forming particles of smaller particle size to improve the impact resistance of the material after high-temperature calcination. Assuming that large-size porcelain-forming particles occupy the eight corners of the cube according to the ideal atomic stacking model, the center and the center of the side of the ideal atomic stacking model can be filled with porcelain-forming particles of smaller particle size. If small-size porcelain-forming particles are filled in the center of the side of the cube, it will be simplified to a plane model: Simplified stacking model 1, from Figure 2 As can be seen from the figure, the diameter of the large-size ceramic particles is set to D 0 , the diameter of the small-size ceramic particles is set as D 1 , then (D 0 ) 2 +(D 0 ) 2 =(D 0 +D 1 ) 2 , calculate the diameter D of small-size ceramic particles 1 =(√2-1)D 0 If the medium-sized ceramic particles are filled into the center of the cube, it is simplified into a plane model: Stacking simplified model 2. As can be seen from the figure, the diameter of the large-sized ceramic particles is set to D 0 , the diameter of the small-size ceramic particles is set as D 1 The diameter of the medium-sized ceramic particles is set as D 2 , then (D 0 +D 1 ) 2 +(D 0 ) 2 =(D 0 +D 2 ) 2 , calculate the diameter D of the medium-sized ceramic particles 2 =(√3-1)D 0 .

[0012] (2) In order to achieve the same porcelain-forming effect for silicone foam materials, peers all add porcelain-forming powder of a single particle size, which can be divided into two situations. The first situation is to add large-particle porcelain-forming powder. In this case, in order to solve the problem that the silicone foam has a certain impact strength after the combustion process, a large amount of large-particle porcelain-forming filler must be added. However, this situation will cause excessive addition of powder, resulting in a large resistance to be overcome during the growth of the foam pores, resulting in a small pore shape, a high density, and poor resilience of the foam. The second situation is to add small-particle porcelain-forming fillers. In this case, small-particle particles will easily agglomerate, causing the viscosity of the rubber to increase too much, the flowability of the rubber to deteriorate, and thus the processing performance to deteriorate. During the foaming process, the rubber is unevenly mixed due to excessive viscosity, resulting in bulging and collapse. The present invention selects the principle of multi-level particle size grading. Compared with adding ceramic fillers with a single particle size, the amount of ceramic filler added can be small, the flowability of the rubber material is good, the impact on the foam cells is small, the foam pore shape is uniform, the pore size is consistent, and it is ensured that the material forms an apparently complete impact-resistant layer during the combustion process.

[0013] (3) The high-temperature calcination process of silicone foam is mainly divided into three stages. In the first stage, the flame retardant powder begins to decompose due to heat. In the second stage, the organic material skeleton decomposes due to heat. In the third stage, the foam material begins to form porcelain after 600°C. Therefore, it is very important to ensure the stability of the material skeleton in the low-temperature stage. By selecting low-temperature fluxes with different melting points to participate in the generation of a continuous phase, in the first stage, the flame retardant powder and the second stage, the organic skeleton decompose in large quantities, and the skeleton particle structure is lost. The flux can melt and fill the grooves to ensure that the material pore structure remains unchanged, ensuring that the material has good high-temperature resistance and heat insulation properties. In the third stage, the modified glass powder serves as a connecting bridge for the porcelain formation point, promoting the porcelain formation of the material, maintaining the surface integrity of the material, and improving the impact resistance of the material.

[0014] (4) The material provided by the present invention can form a complete ceramic body by firing at 800°C for 10 minutes. The surface is smooth and the pore structure is still good after high-temperature calcination. The material has high impact strength and good impact resistance and thermal insulation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a schematic diagram of an ideal atomic stacking model of the present invention;

[0016] Figure 2 Schematic diagrams of stacking simplified model 1 and stacking simplified model 2 of the present invention;

[0017] Figure 3 This is a material structure diagram of the sample in Example 1 of the present invention after calcination at 800° C. for 10 minutes;

[0018] Figure 4 This is the material structure diagram of the sample in Comparative Example 1 after calcination at 800°C for 10 minutes;

[0019] Figure 5 This is the material structure diagram of the sample in Comparative Example 2 after calcination at 800°C for 10 minutes;

[0020] Figure 6 This is the material structure diagram of the sample in Comparative Example 3 after calcination at 800°C for 10 minutes;

[0021] Figure 7 This is the material structure diagram of the sample in Comparative Example 4 after calcination at 800°C for 10 minutes;

[0022] Figure 8 This is the material structure diagram of the sample in Comparative Example 5 after calcination at 800°C for 10 minutes. DETAILED DESCRIPTION

[0023] Hereinafter, a high temperature resistant and impact resistant silicone foam material and a preparation method and application implementation manner provided by the present invention are described in detail.

[0024] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0025] The high temperature resistant and impact resistant silicon foam material of the present application participates in the porcelain forming process by matching the porcelain forming particles of the three-level particle size structure, forming the maximum plane accumulation in the silicon foam organic layer, obtaining enough porcelain forming points, and participating in the generation of the continuous phase by matching the low temperature domain flux with different melting point temperatures. Through the particle size matching and the low temperature domain flux, the phenomenon of the loss of skeleton particles and the formation of cracks caused by the large-scale decomposition of the organic phase is reduced. The silicon foam material after high temperature calcination has a complete pore structure, high temperature resistance and heat insulation, and strong impact resistance. On this basis, the present application is completed.

[0026]

High temperature resistant and impact resistant silicone foam material

[0027] The present invention provides a high temperature resistant and impact resistant silicone foam material, comprising the following raw materials: vinyl silicone oil, hydrogen-containing silicone oil, foaming agent, reinforcing filler, flame retardant filler, ceramic composite filler, inhibitor, catalyst, and optionally color glue.

[0028] In the high temperature resistant and impact resistant silicon foam material provided by the present invention, the high temperature resistant and impact resistant silicon foam material comprises 15-20 parts of ceramic composite filler. Optionally, the weight of the ceramic composite filler is 15-18 parts or 18-20 parts.

[0029] Furthermore, the ceramic composite filler is selected from a combination of modified glass powder, other ceramic fillers, and zinc borate, wherein the other ceramic fillers can be selected from modified mica flakes or modified wollastonite.

[0030] In some embodiments, the mass ratio of the modified glass powder, other ceramic fillers, and zinc borate is (30-35): (55-75): (5-9). Optionally, it can be 30: (55-75): (5-9), (30-35): 65: (5-9), (30-35): (55-75): 5.

[0031] Furthermore, the mass ratio of the modified glass powder, the modified mica flakes and the zinc borate is (30-35):(55-75):(5-9). It can be selected as 30:(55-75):(5-9), (30-35):65:(5-9), (30-35):(55-75):5.

[0032] Furthermore, the mass ratio of the modified glass powder, modified wollastonite and zinc borate is (30-35):(55-75):(5-9). It can be selected as 30:(55-75):(5-9), (30-35):65:(5-9), (30-35):(55-75):5.

[0033] In some embodiments, the modified glass powder is a low temperature glass powder. Preferably, the modified glass powder is divided into three types according to the melting temperature, and the melting temperatures are 350-550°C, 500-700°C, and 600-800°C respectively.

[0034] In some embodiments, the particle size of the modified glass powder is 3000 mesh to 1250 mesh, and can be 3000 mesh to 1500 mesh or 1500 mesh to 1250 mesh.

[0035] In some embodiments, the particle size of the other ceramic fillers is 10 to 40 μm. Optionally, the particle size of the modified mica flakes is 10 to 40 μm. The aspect ratio of the modified wollastonite is 15:1 to 3:1, and the particle size is 10 to 40 μm.

[0036] In some preferred embodiments, the other ceramic fillers are multi-level particle size gradings, and more for example, can be three-level particle size gradings. In the three-level particle size gradings, the first-level particle size structure of the other ceramic fillers is 35-40μm, the second-level particle size structure is 25-29μm, and the third-level particle size structure is 10-16μm. Further preferably, the particle size of the modified mica flakes or modified wollastonite is three-level particle size gradings. In the three-level particle size gradings, the first-level particle size structure of the modified mica flakes and modified wollastonite is 35-40μm, the second-level particle size structure is 25-29μm, and the third-level particle size structure is 10-16μm.

[0037] In some embodiments, the modified mica flakes may be, for example, one or more of phenylsilane-modified mica flakes, alkylsilane-modified mica flakes, or vinylsilane-modified mica flakes, etc. The modified wollastonite may be, for example, one or more of phenylsilane-modified wollastonite, alkylsilane-modified wollastonite, or vinylsilane-modified wollastonite, etc.

[0038] Furthermore, the phenylsilane-modified mica flakes may be one or more of phenyltriethoxysilane-modified mica flakes, diphenyldimethoxy-modified mica flakes, etc.; the alkylsilane-modified mica flakes may be one or more of methyltriethoxysilane-modified mica flakes, n-propyltrimethoxysilane-modified mica flakes, dodecyltrimethoxysilane-modified mica flakes, hexadecyltrimethoxysilane mica flakes, etc.; the vinylsilane-modified mica flakes may be one or more of vinyltriethoxysilane-modified mica flakes, vinyltrichlorosilane-modified mica flakes, vinyltriisopropoxysilane-modified mica flakes, etc.

[0039] Further, the phenylsilane-modified wollastonite may be one or more of phenyltrimethoxysilane-modified wollastonite, phenyltriethoxysilane-modified wollastonite, diphenyldiethoxysilane-modified wollastonite, etc.; the alkyl-modified wollastonite may be one or more of methyltrimethoxysilane-modified wollastonite, methyltriethoxysilane-modified wollastonite, n-propyltrimethoxysilane-modified wollastonite, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, etc.; the vinylsilane-modified wollastonite may be one or more of vinyltrimethoxysilane-modified wollastonite, vinylmethyldimethoxysilane-modified wollastonite, vinyltriethoxysilane-modified wollastonite, vinyltrichlorosilane-modified wollastonite, vinyltriisopropoxysilane-modified wollastonite, etc.

[0040] In some embodiments, the zinc borate particle size is 10-40 μm, and may be 10-30 μm, 30-40 μm, 10-20 μm, 20-40 μm, etc.

[0041] In the high temperature resistant and impact resistant silicone foam material provided by the present invention, the high temperature resistant and impact resistant silicone foam material comprises 20 to 30 parts of vinyl silicone oil. Optionally, the weight parts of the vinyl silicone oil are 20 to 25 parts, 25 to 30 parts, etc.

[0042] Further, the vinyl silicone oil is a methyl vinyl silicone oil with a viscosity in the range of 5000 to 100000 mPa·s. The vinyl molar content of the methyl vinyl silicone oil is 0.06% to 1.0%. Optionally, the viscosity is 5000 to 10000 mPa·s, 10000 to 50000 mPa·s, 50000 to 100000 mPa·s, etc. The vinyl molar content can be, for example, 0.06% to 0.4%, 0.4% to 0.8%, 0.06% to 0.1%, 0.1% to 0.3%, 0.3% to 0.5%, 0.5% to 0.8%, 0.8% to 1.0%, etc.

[0043] In the high temperature resistant and impact resistant silicone foam material provided by the present invention, the high temperature resistant and impact resistant silicone foam material comprises 5-10 parts of hydrogen-containing silicone oil. Optionally, the weight parts of hydrogen-containing silicone oil are 5-8 parts or 8-10 parts.

[0044] Further, the hydrogen-containing silicone oil has a viscosity of 10-500 mPa·s, and a silicon-hydrogen molar content of 0.8% to 1.6%. Optionally, the viscosity is 10-50 mPa·s, 50-100 mPa·s, 100-300 mPa·s or 300-500 mPa·s, etc. The silicon-hydrogen molar content can be 0.8% to 1.2%, 1.2% to 1.6%, 0.8% to 1.0%, 1.0% to 1.2%, 1.2% to 1.4%, 1.4% to 1.6%, etc.

[0045] In the high temperature resistant and impact resistant silicon foam material provided by the present invention, the high temperature resistant and impact resistant silicon foam material comprises 40-50 parts of a foaming agent. Optionally, the weight of the foaming agent can be, for example, 40-45 parts or 45-50 parts.

[0046] Furthermore, the foaming agent is prepared from a nonionic silicone surfactant, dimethyl silicone oil, 107 glue and glass microspheres. The preparation method of the foaming agent is to successively load dimethyl silicone oil, 107 glue and other oil materials into a double planetary agitator in a certain weight ratio for vacuum stirring for 15 to 30 minutes, and then add nonionic silicone surfactant fluorinated silicone oil and 30 to 60 μm glass microspheres into the double planetary agitator for vacuum stirring for 30 to 60 minutes, the stirring temperature is controlled at 20 to 30°C, and the vacuum degree is -0.098MPa. In a specific embodiment, 3 to 40 parts of dimethyl silicone oil and 80 to 120 parts of 107 rubber oil are successively loaded into a double planetary mixer according to a certain weight ratio for vacuum stirring for 15 to 30 minutes, and then 5 to 12 parts of non-ionic silicone surfactant fluorinated silicone oil and 5 to 30 parts of 30 to 60 μm glass beads are added to the double planetary mixer for vacuum stirring for 30 to 60 minutes. The stirring temperature is controlled at 20 to 30°C, and the vacuum degree is -0.098 MPa.

[0047] More preferably, the viscosity of 107 glue is between 500 MPa·s and 50000 MPa·s, and the viscosity of dimethyl silicone oil is between 500 MPa·s and 2000 MPa·s.

[0048] In the high temperature resistant and impact resistant silicon foam material provided by the present invention, the high temperature resistant and impact resistant silicon foam material comprises 5-10 parts of reinforcing filler. Optionally, the weight of the reinforcing filler is 5-8 parts or 8-10 parts.

[0049] Further, the reinforcing filler is selected from one or more of silicon powder, MQ silicone resin, and fumed silica. Optionally, the MQ silicone resin is one of methyl MQ silicone resin and vinyl MQ silicone resin, or methyl MQ silicone resin and vinyl MQ silicone resin.

[0050] In the high temperature resistant and impact resistant silicon foam material provided by the present invention, the high temperature resistant and impact resistant silicon foam material comprises 10-12 parts of flame retardant filler. Optionally, the weight of the flame retardant filler can be, for example, 10-11 parts or 11-12 parts.

[0051] Furthermore, the flame retardant filler is selected from one or more of aluminum hydroxide, magnesium hydroxide, magnesium carbonate, surface silane-modified aluminum hydroxide, and surface silane-modified magnesium hydroxide.

[0052] The high temperature and impact resistant silicone foam material provided by the present invention comprises 0.05-0.2 parts of an inhibitor. Optionally, the weight of the inhibitor may be, for example, 0.05-0.1 parts, 0.1-0.2 parts, 0.1-0.15 parts or 0.15-0.2 parts.

[0053] Furthermore, the inhibitor is an alkynol compound, and the alkynol compound is selected from one of 3-methyl-1-butyn-3-ol, trimethyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynyl-1-cyclohexanol, and 3-phenyl-1-butyn-3-ol.

[0054] In the high temperature resistant and impact resistant silicon foam material provided by the present invention, the high temperature resistant and impact resistant silicon foam material comprises 0.5-2 parts of a catalyst. Optionally, the weight portion of the catalyst is 0.5-1 parts, 1-2 parts, 1-1.5 parts or 1.5-2 parts.

[0055] Furthermore, the catalyst is a Custer platinum catalyst, and the Pt content is 3000-5000 ppm. Optionally, the Pt content may be, for example, 3000-4000 ppm or 4000-5000 ppm.

[0056] In the high temperature resistant and impact resistant silicone foam material provided by the present invention, the high temperature resistant and impact resistant silicone foam material comprises 1 to 2 parts of color glue. Optionally, the weight of the color glue can be, for example, 1 to 1.5 parts or 1.5 to 2 parts.

[0057] Furthermore, the color glue is composed of iron black, silicone oil, aluminum hydroxide and other masterbatch particles, wherein other masterbatch particles can be inorganic pigments such as titanium dioxide, carbon black, iron black, and iron red as pigments uniformly loaded into the silicone rubber matrix material to form a granular colorant.

[0058] The preparation method of the homemade color glue is as follows: vinyl silicone oil or methyl silicone oil and other oils, iron black, aluminum hydroxide and other powders are loaded into a double planetary mixer in a certain weight ratio and fully stirred for 30 to 60 minutes, the stirring temperature is set to 60 to 90°C, and the whole process is evacuated, the vacuum degree is: -0.098MPa, and then inorganic pigments such as titanium dioxide, carbon black, iron black, and iron red are added as pigments into the double planetary mixer and fully stirred for 30 to 60 minutes, and they are evenly dispersed in the silicone oil, the stirring temperature is set to 60 to 90°C, the whole process is evacuated, the vacuum degree is: -0.098MPa, and finally cooled to room temperature, extruded and barreled for use. In a specific embodiment, the preparation method of the homemade color glue is to successively charge 120 to 200 parts of vinyl silicone oil or methyl silicone oil, 8 to 55 parts of carbon black, and 10 to 40 parts of aluminum hydroxide powder into a double planetary mixer in a certain weight ratio and stir them thoroughly for 30 to 60 minutes. The stirring temperature is set to 60 to 90°C, and the whole process is evacuated, and the vacuum degree is -0.098MPa. Then, 6 to 20 parts of titanium dioxide, 9 to 55 parts of iron black, and 3 to 25 parts of iron red as inorganic pigments are added to the double planetary mixer and stirred for 30 to 60 minutes, and they are evenly loaded into the silicone oil. The stirring temperature is set to 60 to 90°C, and the whole process is evacuated, and the vacuum degree is -0.098MPa. Finally, they are cooled to room temperature, extruded and barreled for use.

[0059] [Preparation method of high temperature resistant and impact resistant silicone foam material]

[0060] The present invention also provides a preparation method of a high-temperature resistant and impact-resistant silicone foam material, which comprises: stirring and mixing vinyl silicone oil, hydrogenated silicone oil, a foaming agent, a reinforcing filler, a flame retardant powder, and a ceramic composite filler for the first time, then adding an inhibitor for the second stirring and mixing, and then adding a catalyst, and stirring and mixing for the third time to obtain a uniformly dispersed rubber material; calendering through a coating tool, performing a sulfur curing and a secondary vulcanization reinforcement to obtain a high-temperature resistant and impact-resistant silicone foam material.

[0061] Furthermore, it is preferred that there is also a color glue. The preparation method comprises: weighing 20-30 parts of vinyl silicone oil, 5-10 parts of hydrogenated silicone oil, 40-50 parts of foaming agent, 5-10 parts of reinforcing filler, 10-12 parts of flame retardant powder, 15-20 parts of ceramic composite filler in order by weight, stirring and mixing 1 part of self-made color glue for the first time, then adding 0.05-0.2 parts of inhibitor, stirring and mixing for the second time, and then adding 0.5-2 parts of catalyst, and finally stirring and mixing for the third time to obtain a uniformly dispersed rubber material; the uniformly dispersed rubber material is calendered by a coating tool, and subjected to a sulfur curing and a secondary vulcanization reinforcement to obtain a high temperature resistant and impact resistant silicone foam material.

[0062] In the preparation method of the high temperature resistant and impact resistant silicone foam material provided by the present invention, the temperature of the rubber mixture is controlled within 30°C, the first stirring time is 40 to 80 minutes, the second stirring time is 10 to 30 minutes, and the third stirring time is 3 to 5 minutes.

[0063] In the preparation method of the high temperature resistant and impact resistant silicone foam material provided by the present invention, the primary curing temperature is 80-120° C., and the curing time is 8-10 min; the secondary vulcanization temperature is 150-180° C., and the vulcanization time is 45-60 min.

[0064]

use

[0065] The present invention also provides the use of the high temperature resistant and impact resistant silicone foam material as described above in the present invention and / or the high temperature resistant and impact resistant silicone foam material prepared by the preparation method as described above in the field of protective materials for power battery packs of new energy vehicles.

[0066] The beneficial effects of the present invention are further illustrated below in conjunction with embodiments.

[0067] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with examples. However, it should be understood that the examples of the present invention are only for explaining the present invention, not for limiting the present invention, and the examples of the present invention are not limited to the examples given in the specification. The specific experimental conditions or operating conditions not specified in the examples are made under conventional conditions, or are made under the conditions recommended by the material supplier.

[0068] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0069] In the following examples, unless otherwise specified, various raw materials of the present invention can be purchased from the market or prepared according to conventional methods in the art.

[0070] The preparation method of the homemade color glue is to successively charge 150 parts of vinyl silicone oil or methyl silicone oil, 35 parts of carbon black, and 20 parts of aluminum hydroxide powder into a double planetary mixer according to a certain weight ratio and fully stir for 30 to 60 minutes, set the stirring temperature to 60 to 90°C, and evacuate the whole process with a vacuum degree of -0.098MPa. Then, add 6 parts of titanium dioxide, 45 parts of iron black, and 3 parts of iron red as inorganic pigments into the double planetary mixer and fully stir for 30 to 60 minutes, and evenly disperse them in the silicone oil. The stirring temperature is set to 60 to 90°C, and evacuate the whole process with a vacuum degree of -0.098MPa. Finally, cool to room temperature, extrude and barrel for use.

[0071] The preparation method of the foaming agent is as follows: 40 parts of dimethyl silicone oil and 120 parts of 107 rubber oil are successively loaded into a double planetary mixer according to a certain weight ratio for vacuum stirring for 15 to 30 minutes, and then 10 parts of non-ionic silicone surfactant fluorinated silicone oil and 10 parts of 30 to 60 μm glass beads are added into the double planetary mixer for vacuum stirring for 30 to 60 minutes, the stirring temperature is controlled at 20 to 30°C, and the vacuum degree is -0.098MPa.

[0072] Low temperature glass powder 1 (U-H Chemical Technology Co., Ltd., brand: C4048)

[0073] Low temperature glass powder 2 (U-H Chemical Technology Co., Ltd., brand: C4165)

[0074] Low temperature glass powder 3 (U-H Chemical Technology Co., Ltd., brand: C4065)

[0075] Modified mica flakes 1 (Shenzhen Haiyang Powder Technology Co., Ltd., brand: HY-TM6)

[0076] Modified mica flakes 2 (Shenzhen Haiyang Powder Technology Co., Ltd., brand: HY-PM2)

[0077] Modified mica flakes 3 (Shenzhen Haiyang Powder Technology Co., Ltd., brand: HY-PM5)

[0078] Modified wollastonite 1 (Shenzhen Haiyang Powder Technology Co., Ltd., brand: HY-W06)

[0079] Modified wollastonite 2 (Shenzhen Haiyang Powder Technology Co., Ltd., brand: HY-W10)

[0080] Modified wollastonite 3 (Shenzhen Haiyang Powder Technology Co., Ltd., brand: HY-W08)

[0081] Reinforcement filler (Hubei Huifu Nanomaterials Co., Ltd., brand: HB132)

[0082] Flame retardant powder (Suzhou Shizhinian New Material Technology Co., Ltd., brand: ZH104B)

[0083] Inhibitor (Guangzhou Siyou New Material Technology Co., Ltd., brand: YZJ-17)

[0084] Catalyst (Guangzhou Siyou New Material Technology Co., Ltd., brand: PT3000-SW)

[0085] Example 1

[0086] A high temperature resistant and impact resistant silicone foam material is made of the following raw materials in parts by weight:

[0087] 20 parts of vinyl silicone oil (viscosity 5000mpa·s, vinyl molar content 0.8%)

[0088] 5 parts of hydrogen-containing silicone oil (viscosity 88mpa·s, silicon-hydrogen molar content 0.8%)

[0089] 40 parts of foaming agent

[0090] 5 parts of reinforcing filler

[0091] 10 parts of flame retardant powder (modified aluminum hydroxide, particle size 3000 mesh)

[0092] Ceramic composite filler 15 parts

[0093] 1 piece of homemade color glue

[0094] 0.5 parts of inhibitor

[0095] Catalyst 1 part (3000ppm)

[0096] This embodiment provides a method for preparing a high temperature resistant and impact resistant silicone foam material, comprising the following steps:

[0097] (1) Weigh 20 parts of vinyl silicone oil, 5 parts of hydrogenated silicone oil, 40 parts of foaming agent, 5 parts of reinforcing filler, 10 parts of flame retardant powder, 15 parts of ceramic composite filler and 1 part of self-made color glue in order by weight, add them into a planetary mixer, start stirring, and perform the first stirring and mixing for 40 minutes, then add 0.5 parts of inhibitor, perform the second stirring and mixing for 10 minutes, then add 1 part of catalyst, and finally perform the third stirring and mixing for 3 minutes to obtain a uniformly mixed rubber material. During the above mixing process, the temperature of the rubber material needs to be controlled within 30°C.

[0098] (2) Attach PET release films on the upper and lower sides of the uniformly mixed rubber material in step (1), and calender the rubber material by means of a coating tool. The thickness of the calendered rubber material is controlled to be 1 mm ± 0.15 mm. Then, a sulfur curing and a secondary vulcanization reinforcement are performed. Finally, the release films on the upper and lower sides are removed by an automatic film stripping machine to obtain a high temperature resistant and impact resistant silicone foam material.

[0099] (3) In step (2), the primary sulfur curing temperature is 120°C and the curing time is 8 min; the secondary sulfur curing temperature is 150°C and the sulfur curing time is 60 min.

[0100] The composition of the ceramic composite filler is shown in Table 1

[0101] Table 1 Ceramic composite filler 1

[0102] name Specification Number of copies Low temperature glass powder 1 483℃, 1250 mesh 10 Low temperature glass powder 2 560℃, 1500 mesh 10 Low temperature glass powder 3 770℃, 1250 mesh 10 Modified mica flakes 1 40μm 25 Modified mica flakes 2 24μm 20 Modified mica flakes 3 16μm 20 Zinc borate 30μm 5

[0103] The prepared samples were calcined at 800℃ for 2h. After high temperature treatment, the structure of the ceramic body was Figure 3 As shown in the figure, it can be seen that there are residual lines on the surface of the sample caused by the low-temperature glass powder melting and filling the grooves of the organic framework, and the material has a high impact strength, indicating that a ceramic body has been formed, the material surface is flat, the bubbles are complete, and the bending angle is small.

[0104] Example 2

[0105] The implementation content of a high temperature resistant and impact resistant silicon foam material is basically the same as that of Example 1, except that the mica sheets of different particle sizes in the ceramic composite filler are replaced with wollastonite of different particle sizes.

[0106] The composition of the ceramic composite filler used is shown in Table 2

[0107] Table 2 Ceramic composite filler 2

[0108] name Specification Number of copies Low temperature glass powder 1 483℃, 1250 mesh 15 Low temperature glass powder 2 560℃, 1500 mesh 10 Low temperature glass powder 3 770℃, 1250 mesh 10 Modified wollastonite 1 40μm 25 Modified wollastonite 2 28μm 20 Modified wollastonite 3 10μm 30 Zinc borate 30μm 6

[0109] Example 3

[0110] The implementation content of a high temperature resistant and impact resistant silicone foam material is basically the same as that of Example 1, except that the number of foaming agents is changed to 50 parts.

[0111] Example 4

[0112] The implementation content of a high temperature resistant and impact resistant silicon foam material is basically the same as that of Example 1, except that the number of catalyst parts is changed to 1.5 parts.

[0113] Example 5

[0114] The implementation content of a high temperature resistant and impact resistant silicone foam material is basically the same as that of Example 1, except that the vinyl molar content of the vinyl silicone oil is changed from 0.8% to 1%.

[0115] Test standard:

[0116] Tensile strength, elongation at break: The tensile strength and elongation at break of foam materials are tested according to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".

[0117] Foam density: The density of the foam material is tested according to the standard GBT6343-2009 "Determination of apparent density of foam plastics and rubber".

[0118] Foaming ratio: Pour the rubber material that has been stirred evenly with the addition of the catalyst into a graduated measuring cup quickly, record the material height L0, and after the foaming is complete, record the material height L1 at this time, calculate L1 / L0, and the obtained value is the foaming ratio of the foam.

[0119] Flame retardant performance test: Test the flame retardant performance of the foam according to the UL94 flame retardant grade standard

[0120] Temperature resistance test: refer to GB / T 11835-2016 "Rock wool, slag wool and their products for insulation" test standard, place the silicone foam material on a heating table set at 450°C, apply a certain pressure, and continue heating for 20 minutes. Record the difference between the hot surface temperature and the cold surface temperature of the silicone foam at 20 minutes. The difference can represent the temperature resistance performance.

[0121] Impact resistance evaluation: Take a 2mm thick square sample with a shape of 50*50cm. Place it in a muffle furnace at 800℃ for 10 minutes to observe whether the foam is completely integrated after firing, whether the surface is flat, and the changes in the pore state and bending angle. The evaluation level reference is as follows:

[0122] Impact resistance level 1: complete and integral, smooth surface without cracks, bending angle less than 5°, no cracks when dropped;

[0123] Impact resistance level 2: intact as a whole, slight cracks on the surface, bending angle less than 10°, no breakage when dropped;

[0124] Impact resistance level 3: intact as a whole, slight cracks on the surface, bending angle greater than 10° and less than 20°, no cracks when dropped;

[0125] Impact resistance level 4: intact, with obvious cracks on the surface, or bending angle greater than 20°, and breaking when dropped;

[0126] Impact resistance level 5: Overall cracking, severe surface cracks, or bending angle greater than 30°, and falling breakage.

[0127] The samples prepared in Examples 1 to 5 were tested according to the above test standards, and the performance test results of the samples are shown in Table 3.

[0128] Table 3 Performance test table of Examples 1 to 5

[0129]

[0130]

[0131] It can be seen from the test results in Table 3 that, compared with Example 2, when the amount of ceramic composite filler is the same, the ceramic filler of Example 2 is replaced by wollastonite of different particle sizes instead of mica sheets of different particle sizes, and the impact resistance grade of the silicon foam is 1, and the surface is smooth and free of cracks, and there is no breakage when falling. In addition, the mica sheets are replaced by ceramic composite fillers composed of wollastonite. Due to its needle-rod structure, when the low-temperature glass powder melts and fills the foam cracks during the firing process, the foam can withstand local high-temperature impact. It is fired at a butane torch for 15 seconds at a temperature above 1200°C, with slight cracks on the surface and no burn-through on the back. Examples 3 to 5 increase the amount of foaming agent or the amount of catalyst or change the molar content of silicon hydrogen in hydrogen-containing silicone oil from 0.8% to 1.0% on the basis of Example 1, which can reduce the density of the material and obtain a lower density silicon foam material. The impact resistance of the foam is not affected, and thanks to the low addition of ceramic composite filler, the foam has uniform pores during the foaming process, and the pore structure is complete after firing, and has good thermal insulation performance. It can be seen from Examples 1 to 5 that the ceramic filler follows the principle of three-level particle size matching and selects low-temperature glass powder, which can ensure that the pores of the foam material are uniform when the addition of ceramic filler is low, and after the foam material is calcined, the pore structure is complete and the impact resistance is good.

[0132] Comparative Example 1

[0133] The content of a silicone foam material is substantially the same as that of Example 1, except that the amount of ceramic composite filler added is 0, that is, no ceramic composite filler is added.

[0134] The prepared sample was calcined at 800℃ for 10min, and the structure of the material after calcination was shown in Figure 2. Figure 4 ,It can be seen from the figure that without adding ceramic composite fillers, the surface of the material will crack directly after calcination, and the impact resistance is poor.

[0135] Comparative Example 2

[0136] The content of a silica gel foam material is basically the same as that of Example 1, except that the ceramic composite fillers are replaced with 40 μm mica sheets.

[0137] The prepared sample was calcined at 800℃ for 10min. The material structure after calcination is shown in Figure 5As can be seen from the figure, compared with Comparative Example 1, the surface cracking of the material is improved by adding ceramic composite fillers to the system, and the foam is still a complete whole after calcination, but compared with Example 1, its appearance is poor and the impact resistance is reduced.

[0138] Comparative Example 3

[0139] The content of a silica gel foam material is basically the same as that of Example 1, except that the ceramic composite fillers are replaced with 28 μm mica sheets.

[0140] The prepared sample was calcined at 800℃ for 10min. The material structure after calcination is shown in Figure 6 ,It can be seen from the figure that the surface cracks are further reduced, but there are still cracks on the surface, and it is impossible to achieve a completely flat and smooth surface.

[0141] Comparative Example 4

[0142] The content of a silica gel foam material is basically the same as that of Example 1, except that the ceramic composite fillers are replaced with 16 μm mica sheets.

[0143] The prepared sample was calcined at 800℃ for 10min. The material structure after calcination is shown in Figure 7 , from the picture we can see that there are slight cracks in the material.

[0144] Comparative Example 5

[0145] The content of a silicone foam material is basically the same as that of Example 1, except that the ceramic composite fillers are replaced with 40 μm mica sheets, and the number of added ceramic composite fillers is changed to 30 parts.

[0146] The prepared sample was calcined at 800°C for 10 min. The material structure after calcination is shown in Figure 8 , the material still exists after calcination, and after the amount of ceramic composite filler added increases, the density of the foam material is high, the pores are uneven, and the temperature resistance and heat insulation effect of the material are affected.

[0147] The performance of the samples prepared in Comparative Examples 1 to 5 was tested. The test results are shown in Table 4.

[0148] Table 4 Performance test table of comparative examples 1 to 5 and embodiment 1

[0149]

[0150]

[0151] It can be seen from the test results in Table 4 that, compared with Example 1, in Comparative Example 1, no ceramic composite filler is added to the system, the material completely cracks, the shell is easily broken, and the impact resistance of the material is poor. In Comparative Examples 2 and 3, large-particle mica flakes are added, the flowability of the rubber is improved, the overall viscosity is reduced, the pores are easier to grow, and the density is reduced, but the surface is still not smooth and flat, and cracks still exist. In Comparative Examples 4 and 5, due to the small-particle mica flakes and the increased proportion of ceramic fillers added, the surface cracks are reduced and the surface flatness is improved, but the viscosity of the rubber will increase, resulting in uneven and small pores of the foam, high density, and poor thermal insulation and high temperature resistance of the foam material.

[0152] The present invention provides a high-temperature resistant and impact-resistant silicone foam material and a preparation method thereof. The silicone foam material is resistant to high temperatures, has strong impact resistance, has a small bending angle, has good flame retardancy, has low density, and has good buffering and shock-absorbing performance. It can be used for heat insulation, fire prevention, buffering and sealing, and can be applied to new energy vehicle power batteries and battery sealing and shock-absorbing material components.

[0153] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.

[0154] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A high temperature resistant and impact resistant silicon foam material, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of vinyl silicone oil, 5-10 parts of hydrogen-containing silicone oil, 40-50 parts of foaming agent, 5-10 parts of reinforcing filler, 10-12 parts of flame retardant filler, 15-20 parts of ceramic composite filler, 0.05-0.2 parts of inhibitor, and 0.5-2 parts of catalyst; Among them, the ceramic composite filler is selected from a combination of modified glass powder, other ceramic fillers, and zinc borate; the modified glass powder is low-temperature glass powder; and the other ceramic fillers are multi-level particle size gradations.

2. The high temperature resistant and impact resistant silicon foam material according to claim 1, characterized in that: The mass ratio of the modified glass powder, other ceramic fillers and zinc borate is (30-35): (55-75): (5-9); And / or, the modified glass powder is divided into three types according to melting temperature, and the melting temperatures are 350-550°C, 500-700°C, and 600-800°C respectively; And / or, the particle size of the modified glass powder is 3000 mesh to 1250 mesh; And / or, the other ceramic-forming filler is modified mica flakes or modified wollastonite; And / or, the other ceramic-forming fillers are of three-level particle size gradation; And / or, the zinc borate particle size is 10 to 40 μm.

3. The high temperature resistant and impact resistant silicon foam material according to claim 2, characterized in that: The particle size of the modified mica flakes or modified wollastonite is a three-level particle size distribution; And / or, the modified mica flakes are selected from one or more of phenylsilane-modified mica flakes, alkylsilane-modified mica flakes or vinylsilane-modified mica flakes; And / or, the aspect ratio of the modified wollastonite is 15:1 to 3:1; And / or, the modified wollastonite is selected from one or more of phenylsilane-modified wollastonite, alkylsilane-modified wollastonite or vinylsilane-modified wollastonite. And / or, in the three-level particle size grading, the first-level particle size structure of other ceramic fillers is 35-40 μm, the second-level particle size structure is 25-29 μm, and the third-level particle size structure is 10-16 μm.

4. The high temperature resistant and impact resistant silicon foam material according to claim 3, characterized in that: In the three-level particle size distribution, the first-level particle size structure of the modified mica flakes and the modified wollastonite is 35-40 μm, the second-level particle size structure is 25-29 μm, and the third-level particle size structure is 10-16 μm.

5. The high temperature resistant and impact resistant silicon foam material according to claim 1, characterized in that: The vinyl silicone oil is methyl vinyl silicone oil with a viscosity in the range of 5000 to 100000 mPa·s, and the molar content of vinyl in the methyl vinyl silicone oil is in the range of 0.06% to 1.0%.

6. The high temperature resistant and impact resistant silicon foam material according to claim 1, characterized in that: The hydrogen-containing silicone oil has a viscosity of 10-500 mpa·s and a silicon-hydrogen molar content of 0.8% to 1.6%.

7. The high temperature resistant and impact resistant silicon foam material according to claim 1, characterized in that: The foaming agent is prepared from non-ionic silicone surfactant, dimethyl silicone oil, 107 glue and glass microspheres; And / or, the reinforcing filler is selected from one or more of silicon powder, MQ silicone resin, and fumed silica; And / or, the flame retardant filler is selected from one or more of aluminum hydroxide, magnesium hydroxide, magnesium carbonate, surface silane-modified aluminum hydroxide, and surface silane-modified magnesium hydroxide; And / or, the inhibitor is an alkynol compound, and the alkynol compound is selected from one of 3-methyl-1-butyn-3-ol, trimethyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynyl-1-cyclohexanol, and 3-phenyl-1-butyn-3-ol; And / or, the catalyst is a Custer platinum catalyst, and the Pt content is 3000-5000ppm.

8. The high temperature resistant and impact resistant silicon foam material according to claim 1, characterized in that: The high temperature resistant and impact resistant silicone foam material also includes 1 to 2 parts of color glue, which is composed of iron black, silicone oil, aluminum hydroxide and other masterbatch particles.

9. The method for preparing the high temperature resistant and impact resistant silicone foam material according to any one of claims 1 to 8, characterized in that: The preparation method comprises: stirring and mixing vinyl silicone oil, hydrogen-containing silicone oil, foaming agent, reinforcing filler, flame retardant powder and ceramic composite filler for the first time, then adding an inhibitor for the second stirring and mixing, and then adding a catalyst for the third stirring and mixing to obtain a uniformly dispersed rubber material; calendering the uniformly dispersed rubber material through a coating tool, performing a sulfur curing and a secondary vulcanization reinforcement to obtain a high temperature resistant and impact resistant silicone foam material.

10. Application of the high temperature resistant and impact resistant silicone foam material according to any one of claims 1 to 8 and / or the high temperature resistant and impact resistant silicone foam material prepared by the preparation method according to claim 9 in the field of protective materials for power battery packs of new energy vehicles.

Citation Information

Cited By

  • Modified mica sheet flame retardant and hollow glass bead lightweight flame-retardant material

    CN121136205A